2017
DOI: 10.1128/jvi.01174-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics Highlights the Role of the Activator Protein 1 Transcription Factor in the Host Response to Ebolavirus

Abstract: Ebolavirus and Marburgvirus comprise two genera of negative-sense singlestranded RNA viruses that cause severe hemorrhagic fevers in humans. Despite considerable research efforts, the molecular events following Ebola virus (EBOV) infection are poorly understood. With the view of identifying host factors that underpin EBOV pathogenesis, we compared the transcriptomes of EBOV-infected human, pig, and bat kidney cells using a transcriptome sequencing (RNA-seq) approach. Despite a significant difference in viral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Interferon-ɑ (IFNα), IFNβ and IFNɣ pathways vary in their level of activation between bat and human cells in response to viral infection [49][50][51][52] . Some of these studies have shown dampened immune responses in bats, whereas others have shown heightened responses to infection.…”
Section: Innate Bat Immunitymentioning
confidence: 99%
“…Interferon-ɑ (IFNα), IFNβ and IFNɣ pathways vary in their level of activation between bat and human cells in response to viral infection [49][50][51][52] . Some of these studies have shown dampened immune responses in bats, whereas others have shown heightened responses to infection.…”
Section: Innate Bat Immunitymentioning
confidence: 99%
“…These results reflect the possible dramatic change of the characteristics of cell cultures within a very short time. Although the vast majority of cell culture experiments in filovirus research, including model systems for entry and replication, are performed with immortalized cell lines [36,[41][42][43][44][45][46][47][48][49], the limitations of these model systems should be taken into consideration. We have also demonstrated the importance of the use of cells in low passage numbers not taken into consideration in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of EBOV entry and infection processes in bat cells have predominantly been performed in immortalized cell lines [36,[41][42][43][44][45][46][47][48][49]. For the purpose of having an informative cell culture model system we intended to derive primary and immortalized cell cultures from various organs of M. condylurus bats.…”
Section: Introductionmentioning
confidence: 99%
“…Viruses. Recombinant wild-type EBOV, strain Mayinga, was recovered from the full-length clone and support plasmids in HEK 293T cells and passaged twice in Vero E6 cells for amplification 29 . Recombinant wild-type MARV, strain Uganda, was recovered similarly in BHK-21 cells 89 and passaged twice in Vero E6 cells for amplification.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Some studies claim both EBOV and MARV replicate to similar levels in ERB and human derived cell lines 26 , with a robust innate immune response mounted by ERB and to a lesser degree, human cells, while others claim MARV inhibited the antiviral program in ERB cells, like in primate cells, and did not induce almost any IFN gene 27 , or little anti-viral gene induction 28 . An experiment with the pig (PK15A) and bat (EhKiT) cells suggested they responded to EBOV through the upregulation of immune, inflammatory, and coagulation pathway, in contrast to a limited response in the human (HEK293T) cells 29 . To comprehensively understand the pathways involved in the bat filoviral response, we infected bats, rather than their isolated cells, and analyzed tissue-specific RNA expression through mRNA-seq in the organs of the infected animals.…”
Section: Introductionmentioning
confidence: 99%